EKSISTENSI PENERAPAN HUKUM TERHADAP PERALIHAN HAK PENGUASAAN TANAH DITINJAU DARI UNDANG-UNDANG POKOK AGRARIA NO 5 TAHUN 1960 DALAM RANGKA PENDAFTARAN TANAH PERTAMA KALI - Lamhot Hutahaean (PT Sanagi Edu Konsultan, 2025)
Land ownership is the right to have freedom for the owner of the land to be able to use his land for his needs as long as he does not do things that are contrary to the provisions of the laws and regulations. Control of land does not mean that someone who controls it is recognized by the State as a person who has the right to the land, land ownership must be proven by legal evidence. The community who recognizes that the land is theirs but does not have a certificate, so that control of the land is proven by other legal evidence such as an Authentic Deed. According to Government Regulation Number 24 of 1997, the implementation of land rights registration includes the activities of Land Registration for the first time (initial registration) and Land Data Maintenance (maintenance). Land registration for the first time is carried out through Systematic land registration and Sporadic land registration. The transfer of control of land that has not been certified is carried out before a Notary as a legal service provider, as long as the evidence is an authentic deed, and every land right that does not have a certificate must be registered immediately. This research uses a type of normative legal research that examines in depth and explicitly which is used as a reference to find out a concrete legal analysis regarding the problem being researched.